Effect of anti-tuberculosis drugs on hematological profiles of tuberculosis patients attending at University of Gondar Hospital, Northwest Ethiopia. Issue 1 (December 2016) - Kassa, Eyuel; Enawgaw, Bamlaku; Gelaw, Aschalew; Gelaw, Baye
Abstract Background Tuberculosis (TB) treatment may present significant hematological disorder and some anti-TB drugs also have serious side effects. Although many other diseases may be reflected by the blood and its constituents, the abnormalities of red cells, white cells, platelets, and clotting factors are considered to be primary hematologic disorder as a result of tuberculosis treatment. The aim of this study was to determine hematological profiles of TB patients before and after intensive phase treatment. Objective The aim of this study was to determine hematological profiles of TB patients before and after intensive phase treatment. Methods Smear positive new TB patients were recruited successively and socio-demographic characteristics were collected using pre-tested questionnaire. About 5 ml of venous blood was collected from each patient and the hematological profiles were determined using Mindry BC 3000 plus automated hematology analyzer. Result The hematological profiles of TB patients showed statistically significant difference in hematocrit (38.5 % versus 35.7 %), hemoglobin (12.7 g/lversus11.8 g/l) and platelet (268 × 103 /μlversus239 × 103 /μl) values of patients before initiation of treatment and after completion of the intensive phase of tuberculosis treatment, respectively (P  < 0.05). The red cell distribution width (RDW) of treatment naïve TB patients was by far lower (17.6 ± 7.09 %) than the corresponding RDW (31.9 ± 5.19 %) of intensive phase treatment completed patients. Among TB patients that had high platelet distribution width (PDW) (n  = 11) before initiation of TB treatment, 10 demonstrated lower PDW values after completion of the intensive phase. There was no significant difference on total white blood cell count among TB patients before and after completion of the 2 month treatment. Conclusion The levels of hemoglobin, hematocrit and platelet count of the TB patients were significantly lowered after completion of the intensive phase of TB treatment. Significant variation of the RDW and PDW were also observed among treatment naïve and treatment completed patients. Hematological abnormalities resulted from TB treatment should be assessed continuously throughout the course of tuberculosis therapy.